DNAR-12. COMBINING TUMOUR TREATING FIELDS WITH THERAPEUTIC DNA DAMAGE RESPONSE INHIBITORS TO INCREASE POTENCY IN HIGH-GRADE GLIOBLASTOMAS USING CLINICALLY RELEVANT EX-VIVO GLIOMA STEM CELL MODELS. (14th November 2022) - Vanderlinden, Aurelie; Rominiyi, Ola; Collis, Spencer; Jones, Callum; Myers, Katie; McGarrity - Cottrell, Connor
Abstract: High-grade gliomas are the most common and aggressive type of primary brain cancer. Despite maximal surgical resection, followed by chemotherapy and radiotherapy, overall survival for patients remains between 10-16 months, with limited improvement in survival rates over the last 40 years. This highlights an urgent unmet clinical need to develop more effective therapeutic interventions for these devastating tumours.Tumour-Treating Fields (TTFields), which deliver low-intensity (1–3V/cm) intermediate-frequency (100–300kHz) alternating electric fields to localised tumour sites, represents an exciting new clinically-approved fourth modality for the treatment of high-grade gliomas, with randomised clinical trial evidence supporting improved overall survival (20.9 vs 16.0 months). Whilst TTFields are primarily thought to mediate their anti-cancer effects by disrupting mitotic tubulin dimer alignment leading to abnormal chromosomal segregation and mitotic cell death, recent data suggests that TTFields may also attenuate DNA damage repair efficiency and replication fork dynamics. We therefore hypothesised that combining TTFields with therapeutic DNA damage response inhibitors (DDRi), to develop next generation multimodal therapy regimes, would enhance TTFields potency in glioma cells either alone, or in combination with current standard-of-care chemoradiotherapy. To assess this, we employed clinically-relevant patient-derived primary glioma stem cell (GSC) models that represent both inter-patient and intra-tumoural heterogeneity, including unique ex-vivo models of post-surgical residual disease. We show that combining TTFields with radiation and clinically approved PARP inhibitor therapy leads to significantly increased amounts of DNA damage with concurrent decreased clonogenic survival in GSCs. Furthermore, we have shown similar impressive potency when TTFields treatments are combined with ATR inhibitors that are currently being assessed in various global clinical trials for other cancers. Overall, these exciting findings support further assessment of TTFields and DDRi combinations to underpin future clinical trials combining TTFields with clinically approved DDRi to improve outcomes for patients with currently incurable high-grade gliomas.